Quantitative Evaluation of Participating Students and Cooperating Residents of the Service Learning Program - Oracion, Enrique G. (Silliman Journal, 2022)
This article is a quantitative assessment of the experiences of students in the service-learning program. The evaluation supports the reflections they have written in their journals and incorporated in the reports of individual faculty coordinators. The evaluation of students shows that there exist positive or direct relationships among the following areas of their experiences: skills and knowledge from classroom instruction, services extended to the community, practical learning gained in community service, and value realization. Also included in this evaluation is the impact of the program on the community residents. Majority of the cooperating residents who availed of the program were females and the capacitating projects they ranked highest in terms of importance are training in food processing and teamwork building. Of the health projects introduced into the community, the lectures on family planning, breast cancer detection, and urinalys were considered of immense importance by the participating residents. The cooperating residents and the participating students recommended that the service-learning program should continue.